Evaluation of Mangrove Area Changes and Fisheries Production in South Lampung Coastal: Spatio-Temporal Analysis - Citra, Lalik Salistia; Handayani, Muliawati; Nuzapril, Mulkan (Universitas Gadjah Mada, 2026)
Mangrove ecosystems play an important role in supporting the productivity of coastal capture fisheries by providing habitats, spawning grounds, and nursery areas for various fish species, as well as by facilitating ecological connectivity with adjacent coastal waters. This study aims to evaluate changes in mangrove cover in South Lampung Regency during 2020-2023, examine the variability of capture-fisheries production, and analyze the statistical relationships among these variables. The methods employed include multitemporal spatial analysis of Landsat 8 imagery using supervised classification and NDVI calculations, combined with statistical analyses based on Pearson correlation and simple linear regression, using fisheries production data obtained from the Department of Marine and Fisheries. The results indicate that mangrove cover increased from 475.5 ha in 2020 to 551.9 ha in 2023, in line with rehabilitation programs implemented in several coastal districts. During the same period, capture fisheries production reached 125,168 tons, dominated by squid, scads, yellowtail scads, anchovies, groupers, swimming crabs, and white shrimp. Statistical analysis revealed a powerful relationship between mangrove expansion and the catches of several key fisheries commodities. These findings are consistent with previous studies highlighting the importance of mangrove ecosystems for fisheries productivity and emphasize the role of mangrove conservation in supporting sustainable capture fisheries and coastal management in South Lampung Regency.